(untitled) (Research, Society and Development, 2021)
The objective of this work was to carry out a bibliographic research on the use of agro-industrial waste as a substrate for the production of microbial lipase, identifying the main microorganisms, fermentation time and the inclusion of inducers in the medium. Thirty papers were selected and formed a database. Research in Brazil accounted for 60% of the publications used, the palm oil and soy residue (cake and sludge) were the most reported representing 13.3%, the filamentous fungi were the most studied, the Aspergillus genus was the most found totaling 36.6 % and in particular the species A. niger, which was studied by eight researchers. Regarding the time, fermentations ranged from 20 to 336 h, and the time of 48 h was used by seven researchers. Among the 30 publications it was possible to verify that in 13 (43%) of them the authors did not use any type of inducer to supplement the agro-industrial residue, however the use of lipid sources and mainly of nitrogen significantly increased the production of lipase. Most surveys were conducted in FES (73.3%). Using agro-industrial waste and supplementing the environment with lower priced inductors, in addition to boosting production can make the final product cheaper.